Connecting Rod with Enhanced Performance through Fast and Precise Bolted Joint Design Methodology - Da Silva, Rafael Aguera Rezeno [UNESP]; De Souza Rodrigues, Alex [UNESP]; Tomazini, José Elias [UNESP]; Martins, Marcelo Sampaio [UNESP]; Silva, Kauê Cruz; Santos, Michele (SAE International, 2016)
Connecting rod joint optimization is a well-known design procedure used for new cranktrains, not only for truck applications, but also for passenger cars. Big end bolted joint is one of the most critical connecting rods regions under engine operation, especially due to joint opening phenomenon and consequent engine failure. Thus, in order to have a robust design, it is usually applied safety factors to absorb this design margin. However, due to the continuous increase of engine loads to attend different emission regulations, this design condition became a vital parameter for connecting rods. thyssenkrupp developed a joint evaluation methodology to be applied during conrod design, presenting better accuracy when compared to the standard development procedure, the VDI 2230 part 1, thus leading to better performance for real engine application. This approach combines the VDI design algorithm with a simple and fast finite element model for force and moment extraction. To validate it, the present work compares thyssenkrupp joint design methodology with VDI2230 part 1 approach and with a non-linear numerical model, which evaluates the joint behavior by means of a finite element analysis with frictional contacts and parallel threaded bolts.